Intestinal mucosal MMP-1 – a prognostic factor in colon cancer. (May 2013) - Langenskiöld, Marcus; Ivarsson, Marie-Lois; Holmdahl, Lena; Falk, Peter; Kåbjörn-Gustafsson, Christina; Angenete, Eva
Abstract Objective. There is evidence that transforming growth factor-β1 (TGF-β1) and matrix metalloproteinases (MMPs) play an important role in tumor invasion and progression in colorectal cancer. The aim of this study was to assess their utility in prediction of cancer-specific survival (CSS). Materials and methods. 136 patients undergoing curative surgery for colorectal carcinoma were prospectively included. Samples were taken from tumor and tumor-free intestinal mucosa and ELISA was used to assess protein levels in the tissues. Patients were followed for CSS. The median follow-up time for all included patients was 65 months (range: 45–92). The main outcome measure was CSS. Results. T stage, lymph node involvement and high levels of MMP-1 as well as MMP-9 in tumor-free mucosa tissue were significantly associated with CSS in colon cancer in univariate analysis. This prognostic strength was maintained for MMP-1 and N-status in multivariate analysis. Conclusions. The results indicate that MMP-1 is independently associated with CSS in patients with colon cancer. Furthermore, a possible clinical implication is that MMP-1 protein expression in tumor-free mucosa could identify colon cancer patients with poor CSS in need of more intensified adjuvant treatment.